اعتماد الحكام الرياضيين على وسائل الاعلام في اكتساب المهارات التحكيمية - سعد براهيمي; الطيب بن الصادق; د/محمودي نادية (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة الدراسة الحالية و التي هي اعتمادالحكامالرياضيينعلىوسائلالاعلامفياكتسابالمهاراتالتحكيمية( دراسةميدانيةعلىحكامالرابطةالولائيةلكرةالقدمبالأغواط )، انطلقت من التساؤل مامدىاعتمادحكامالرابطةالولائيةلكرةالقدمالاغواطعلىوسائلالاعلامفياكتسابالمهاراتالتحكيمية؟ تهدفالدراسة الى التعرفعلى مدى اعتماد حكام الرابطة الولائية لكرة القدم الاغواط على وسائل الاعلام في اكتساب المهارات التحكيمية، كما اهتمت بالرياضة بشكل عام وبموضوع التحكيم في المنافسات الرياضية بصفة خاصة، ولما له من اهمية بالغة في تسيير النشاطات الرياضية ونحاجها كون ان كل المنافسات تحتوي على فريقين او أكثر، فموضوع التحكيم الرياضي موضوع واسع وشاسع الا ان البحث حصره في موضوع التحكيم في كرة القدم ومدى اهتمام وسائل الاعلام به. كما تم الاعتماد على المنهج الوصفي وأداة جمع البيانات التي تمثلت في دليل المقابلة،حيث تكون مجتمع البحث من حكام الرابطة الولائية لكرة القدم والبالغ عددهم 50 حكما وحكمة، ومن خلال عرض وتحليل ومناقشة نتائج دليل المقابلة توصلنا الى تحقق فرضيات دراستنا: ‌أ) يشاهد حكام الرابطة الولائية لكرة القدم بالأغواط الوسائل الإعلامية بدافع التعلم واكتساب خبرات جديدة من خلال لتغطيها للبرامج الرياضية ‌ب) تساعد الوسائل الإعلامية حكام الرابطة الولائية لكرة القدم بالأغواط في اكتساب مهارات تحكيمية جديدة من خلال الحالات التحكيمية التي يتم بثها عبرها. Summary : The current study, which is the dependence of sports referees on the media in acquiring arbitration skills (a field study on the referees of the State Football Association of Laghouat), was launched from the question: To what extent do referees of the State Football Association of Laghouat depend on the media in acquiring arbitration skills? The study aims to identify the extent to which referees of the Laghouat State Football Association rely on the media to acquire refereeing skills. It also focused on sports in general and the issue of refereeing in sports competitions in particular, and because of its great importance in the management of sports activities and their goals, given that all competitions contain Two or more teams. The subject of sports arbitration is a broad and vast subject, but the research is limited to the subject of arbitration in football and the extent of the media’s interest in it. We also relied on the descriptive approach and the data collection tool represented in the interview guide, where the research community consisted of 50 state football association referees, male and female, and through presenting, analyzing and discussing the results of the interview guide, we achieved the verification of the hypotheses of our study: A) The referees of the State Football Association in Laghouat watch the media for the purpose of learning and gaining new experiences through their coverage of sports programs. B) The media helps the referees of the Laghouat State Football Association in acquiring new refereeing skills through the refereeing cases that are broadcast through them.
دراسة ميدانية على حكام الرابطة الولائية لكرة القدم بالاغواط